Propranolol as First-Line Treatment in Orbital Infantile Haemangiomas: A Case Series. (June 2014) - Levitt, M.; Coumou, A. D.; Groeneveld, L.; Freling, N. J. M.; van der Horst, C. M.; Saeed, P.
Abstract Purpose: To highlight the importance of Magnetic Resonance Imaging (MRI) and the use of propranolol as both a final diagnostic tool and adequate treatment for orbital Infantile Haemangiomas (IHs). Methods: A retrospective study was conducted using a case series of 5 infants diagnosed with orbital IH. All patients presented with progressive unilateral proptosis and were at high risk of developing amblyopia, some had combined swelling of the eyelid, impaired eye movements or exposure keratopathy. Propranolol was administered in an initial dose of 0.6 mg/kg/day orally divided in three daily doses and increased in 4 days to 2.7 mg/kg/day. MRI was performed in all children. Results: Striking MR characteristics of an IH lesion were seen in each of our 5 cases, including the presence of flow voids, high contrast enhancement, hypo-intense T1W signal, iso- to hyper intense T2W signal, and lobulated appearance. All patients showed a quick clinical response to treatment, resulting in significant reduction in tumour size within a range of 1--3 weeks and almost complete regression of the lesion at the end of the treatment schedule. Conclusions: Our study adds another 5 cases to the growing body of reports confirming the efficacy and safety -- under controlled circumstances -- of propranolol therapy in orbital IH management, in which we highlight the use of propranolol as both a final diagnostic tool and as an adequate treatment.